The Challenge of Pancasila in Fair Law Enforcement - Nurkhasanah, Finda Hastin (Faculty of Law, Universitas Negeri Semarang, 2022)
Pancasila has become a nation of Indonesia as the basis of the agreement of the Republic of Indonesia. Pancasila as the outlook of the nation need to be implemented in everyday life, this has been exemplified by the founders of the nation through hard work and struggle that resulted in the independence of Indonesia. Growing concerns the legal conditions that favor so much of the element of justice makes the thought keen to discuss whether the values taught by the pancasila is still disregarded or ignored. Pancasila which is the ideology of the nation as a way of life and the foundation in the activities of society, nation and state were impressed only used rote without application was included in the legal field. The quality of a country that became the benchmark guarding against the ideology of the nation's highly anticipated to control the implementation of the law with justice is based on the noble values of pancasila. All legislation must be an elaboration of the principles of pancasila. All laws and regulations that are inconsistent with pancasila, null and void. Therefore, in order to understand the accuracy of a legislation then it should be understood by studying the concepts, principles and values contained in pancasila.